High-coverage ancient genomes reveal divergent population histories and prehistoric starch-related genetic variation in Japan - Koji Ishiya; Fuzuki Mizuno; Jun Gojobori; Masahiko Kumagai; Yasuhiro Taniguchi; Osamu Kondo; Masami Matsushita; Takayuki Matsushita; Li Wang; Kunihiko Kurosaki; Shintaroh Ueda (Proceedings of the National Academy of Sciences, 2026)
Prehistoric population movements played a central role in shaping the genetic diversity across Eurasia. As the eastern terminus of the Eurasian continent, the Japanese archipelago provides a pivotal context for reconstructing the genetic interplay between prehistoric indigenous lineages and continental migrations. However, high-resolution genomic evidence from mainland Japan is limited due to poor DNA preservation. In the present study, we report two low-contamination, high-coverage ancient genomes from mainland Japan, namely an Initial Jomon individual (>67-fold) and a Middle Yayoi individual (>46-fold). The genomes enabled diploid genotyping and individual-level demographic inferences at unparalleled resolutions. Demographic reconstructions revealed that while both lineages underwent population contractions during the Last Glacial Maximum (LGM), their subsequent trajectories diverged; the Jomon lineage was characterized by long-term postglacial stability with no discernible expansion, whereas the Yayoi-related ancestral population exhibited gradual and sustained growth. Our analysis further identified a distinct genetic continuity between the Middle Yayoi and present-day mainland Japanese, refining the evolutionary trajectory of modern genetic profiles. Furthermore, the genomic profile of the Yayoi individual reflected a complex ancestral background shaped by continental interactions before their arrival on the archipelago. Notably, the higher salivary amylase ( AMY1 ) copy number observed in the Initial Jomon individual suggests that AMY1 copy number variation, potentially relevant to starch-rich diets, was already present before the large-scale expansion of rice farming in the Japanese Archipelago. Collectively, the findings demonstrate that high-coverage ancient genomic approaches can provide a powerful framework for deciphering the contrasting population histories and evolutionary trajectories of human lifestyles.